PRODUCTION, TRANSPORT AND DEPOSITION OF SEDIMENTS IN SOME VALLEYS OF GEBEL AL AKHDAR- NORTH -EASTERN LIBYA (Libya Journal of Geographical Studies, 2024)
Three valleys were selected for detailed study: Al-Athrun, Morgs, and Al-Rejel. This study aims to explore how sediments are produced, transported, and deposited, and to attempt to identify any changes in the river environment of the Gebel Al Akhdar valleys. The researcher concluded, through analyzing the data of this study, that in addition to climate changes and river slope processes, there was an additional geological factor that affected the fine/coarse sedimentation cycles, which is the presence of different groups of joints that enhanced the production of rocks, gravel, and soil. From a climatic point of view, rainstorms also eroded rock masses on the sides of the Gebel valleys, which led to the deposition of sediments in the stream as slope debris (a mixture of fine and coarse sediments). The geomorphological processes that occurred before, during, and after the process of deposition of terrace sediments must have been different during each era, as river sediments alternated, mass movement, and the slope washed and valleys sediments. With the alternation of climatic conditions in the Mediterranean region between cold and warm phases, and between wet and dry conditions, changes in the geomorphological environment affected the river systems in the Gebel valleys.
Keywords: river sediments; sediments of the Gebel Al Akhdar valleys